Comparative Study on Electrochemical Treatment of Cyanide Wastewater - Lei, Siming; Song, Yonghui (Frontiers in Chemistry, 2021)
The electrochemical treatment of wastewater is widely used for cleaning due to its efficiency. In this paper, two-dimensional (2D) and three-dimensional (3D) electrochemical systems were used to treat cyanide wastewater. The effect of the applied voltage and the material of the main electrode on the removal of various ions and the characteristics of chemical reactions were mainly studied. The results show that the applied voltage was the key effect of the electrochemical treatment process. The removal of ions from the wastewater at 2 V is mainly due to the effect of electro adsorption and enrichment precipitation, while at 4 V, it is mainly due to anodization and cathodic deposition. The treatment effect of the 3D electrode system was significantly better than the 2D system. The 3D electrode system by used granular activated carbon as the particle electrode, with the carbon filled stainless mesh (CM) and coal based electrode (CB) as the main electrode, the treatment effect were better than main electrode of stainless steel mesh (M). The 3D system with CB as the main electrode had an applied voltage of 4 V, a treatment time of 5 h, plate spacing of 10 mm, and the dosage of activated carbon particles was 2 g. The removal rates of CNT, Cu, Zn, CN−, and SCN− were 94.14, 94.53, 98.14, 98.55, and 93.13%, respectively. The main reaction in anode was the electroly oxidation of CN− and SCN−, while the electrolytic deposition of Cu, Zn, and other metal ions in the cathode surface. There were not only adsorption and electric adsorption of various ions, but also an electrolytic deposition reaction of Cu, Zn, and other metal ions on the surface of the activated carbon particle electrode. During the electrochemical reaction, the concentration of hydrogen ions near the anode increases locally, which produces the precipitation of CuSCN, Cu2Fe(CN)6, and Zn2Fe(CN)6, etc. in the solution, which are helpful for the removal of cyanide and heavy metal ions in cyanide wastewater.